2015
DOI: 10.1093/jac/dkv403
|View full text |Cite
|
Sign up to set email alerts
|

HCV NS3 sequencing as a reliable and clinically useful tool for the assessment of genotype and resistance mutations for clinical samples with different HCV-RNA levels

Abstract: HCV-NS3 sequencing provides reliable results and at the same time gives two clinically relevant pieces of information: a correct subtype/genotype assignment and the detection of variants that may interfere with the efficacy of PI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…The NS3 V36L variant carried by patient HCV17 confers resistance to BOC and possibly to TVR or SMV and is reported to be present in 0.5% of all previously studied worldwide HCV1b strains [ 46 ]. An Italian study of 326 HCV-infected patients treated with TVR/BOC triple therapy, showed this NS3 V36L variant in only two HCV1b patients with SVR [ 14 ], in line with our observations. The two isolates from HCV06 and HCV19 patients carried mutations for TVR ( NS3 I132V) and DSV ( NS5B C316N).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The NS3 V36L variant carried by patient HCV17 confers resistance to BOC and possibly to TVR or SMV and is reported to be present in 0.5% of all previously studied worldwide HCV1b strains [ 46 ]. An Italian study of 326 HCV-infected patients treated with TVR/BOC triple therapy, showed this NS3 V36L variant in only two HCV1b patients with SVR [ 14 ], in line with our observations. The two isolates from HCV06 and HCV19 patients carried mutations for TVR ( NS3 I132V) and DSV ( NS5B C316N).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, it has become clear that more accurate subtyping results can be obtained through the analysis of more diverse regions, such as the NS5B gene [ 11 , 12 , 13 ]. Recently, Di Maio et al [ 14 ] reported that HCV NS3 sequencing, followed by phylogenetic analysis, also improves the specificity and sensitivity of subtype assignments.…”
Section: Introductionmentioning
confidence: 99%
“…As we have previously reported, in view also of the outstanding cost of DAA‐based regimens, a precise and definite assessment of HCV genotype and subtype is mandatory in order to avoid mistreating during the first DAA course. In this context, HCV sequencing should be considered as the best method for subtype/genotype assignment . Another possible explanation for our unusual high rate of breakthrough/non‐responders is the possible presence of pretreatment natural RASs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Di Maio et al reported that NS3 sequencing can reliably detect HCV genotypes/subtypes and successfully used NS3 sequencing in a clinical setup to determine HCV genotype/subtype and the identification of protease inhibitor resistant variants (Di Maio et al, 2016). Previously another group compared NS3 sequencing to NS5B sequencing for genotyping and confirmed that NS3 sequencing is equally valuable (Besse et al, 2012).…”
Section: Discussionmentioning
confidence: 99%